Best practice Islamization of science on Gestalt-Profetik (G-Pro) guidance and counseling model - Rahman, Imas Kania; Kasman, Rusdi (Ibn Khaldun Journal of Social Science, 2019)
Gestalt Prophetic Guidance and counselling (BK G-Pro) is a reconstruction model toward the concept and therapy concept of Gestalt Fredrick S. Perls. It is aimed as a concept of awareness, concept and support which covers many internal dialogue games like empty chair and doing the rounds. BK-G PRO is distinctively known as full awareness, full contact and full support that lead every individual being aware of his existence as Abdullah and Khalifatullah on the earth. The best practice of this model applies group guidance and individual counselling strategy. Group guidance strategy conducted in the form of small group in giving a basic therapy and guidance to all the counselee through The SDBHSM card game. This game is an interactive game between counsellor and counselee and it is aimed to support the counselee to change his condition from being weak awareness to be a full awareness. SDBHSM is stands for S: Siapakah anda (who are you?), D: Darimana anda berasal (where are you from). H: Hendak Ke mana tujuan anda (what is your life aim) S: Sedang apa anda saat ini (what are you doing?). M: manfaat apa yang anda peroleh? (What is the benefit you get?). After group guidance strategy done, the internal dialogue game as individual strategy is implemented. There are 7 advantages of implementing BK G pro model for the counselee. The first, it can develop the self awareness admitting his existence as the creature of Allah the almighty. The second, this model gradually leads the counselee to be grateful, patient and wise in taking life lesson from the experience he has. the third, it can independently develop counselee’s life skill to fulfil his life needs without breaking Islamic law and human rights. The fourth, this model much more focuses on maintaining the heart with its willingness and feeling. The fifth, this model teaches the counselee to be responsible of what he has committed and also willing to accept any consequences of his choice and action. The sixth, the counselee can move from being dependent supported by others to be independent supported by himself and Allah. The seventh, the counselee will consider that he needs others and be able to help other for the sake of Allah.